The Effect of Washback on EFL Learners’ Performance: Impact and Consequences - Djebbar, Houda (Journal of Social Sciences and Humanities, 2021)
Language researchers appear to steadily acknowledge that the field of language testing seems to be a relatively new trend that has entered the field of applied linguistics and didactics. Washback, or the impact of tests on teaching, has become a major area of research since it influences the way teachers teach, select materials, design courses, and test. In the quest of investigating what may be the causes of the low achievement rates within university students; this paper will be proposed to investigate the effects tests have on both the teaching of speaking and the overall learners’ proficiency. This study is carried out to rise teachers’ awareness of the washback phenomenon, and will accompany learners throughout the term with facilitating strategies that will help them develop their language performance. To this end, a case study will be conducted on second-year LMD students at Tlemcen University. Besides, teachers’ questionnaire, and proficiency tests were employed. Results reveal that there is an ambiguity on how tests influence learners’ oral proficiency depending on the teaching methodology followed by the teachers. Eventually, based on the results achieved a number of activities will be proposed for a better teaching/learning environment.